Entrepreneurship-Based Economic Education: Enhancing the Young Generation's Ability to Deal with Job Market Uncertainty in the Digital Era - Muammar Revnu Ohara; Yeni Yeni; Ni Nyoman Suarniki; Dewi Setiawati (PT. Hafasy Dwi Nawasena, 2025)
The rapid development of digital technology has changed the structure of the economy and labor market patterns, requiring the younger generation to have adaptive and innovative skills. The uncertainty of the labor market in the digital era requires the integration of economic education with an entrepreneurial approach to strengthen competitiveness. This study aims to analyze the role of entrepreneurship-based economic education in enhancing the ability of the younger generation to cope with labor market dynamics. The method used is a literature review with a systematic search of journal articles, academic books, conference proceedings, research reports, and education policy documents. Literature sources were obtained from Google Scholar, Scopus, and ScienceDirect using the keywords entrepreneurship-based economic education, youth skills, labor market uncertainty, and digital era. The findings indicate that entrepreneurship-based economic education positively contributes to developing adaptive skills, creativity, and self-confidence among the younger generation, enabling them to respond to rapid changes in the digital labor market. The conclusion emphasizes that integrating entrepreneurship into economic education should be a priority in the curriculum to prepare graduates not only as job seekers but also as job creators. The implications of this research encourage the design of higher education programs that are responsive to the challenges of the digital economy and technological disruption.